The influence of new syllabus and factors affecting student’s academic performance / Mohd Aidil Riduan Awang Kader, Musramaini Mustapha and Suhanom Mohd Zaki - Awang Kader, Mohd Aidil Riduan; Mustapha, Musramaini; Mohd Zaki, Suhanom (Universiti Teknologi MARA Cawangan Pahang, 2020)
This study aims to examine the impact on the new syllabus towards the students’ academic performance and to investigate the factors such as study habits, study self-concept, stress, and English Language and Communication (ELC) affecting the students’ academic performance on Fundamentals of Management course. A total of 243 respondents from the Diploma in Accountancy UiTM Pahang Jengka Campus has participated in this study who were first semester students. A questionnaire survey was employed and descriptive analysis was conducted to analyze the data by using SPSS version 21. The results of this study discovered that the faculty is unable to sustain the 0% failure rate as compared to the previous semester due to modifications to the syllabus. The self-study concept indicated as the most significant factors that contribute to the students’ academic performance with the overall mean score is 3.36. The study also revealed that study habits, stress, and ELC are important factors in determining students’ academic performance in this course. This study is expected to assist the university in formulating and revising the syllabus in line with the students’ ability and understanding of this course. Also, it can provide a guideline and control mechanism especially for the lecturers in the teaching and learning process to ensure the course will be delivered excellently which will lead to improving students’ academic performance.